The Effect of Adding Manure to Organic Mulch Sheets on the Growth and Yield of Crops (Lactuca sativa) Lettuce Plants - Hadiansyah, Bayu Adrian; Machmudi; Ishartati, Erny (Universitas Muhammadiyah Malang, 2023)
The study conducted in Cikajang District, Garut Regency, from February 20 to June 15, 2023, aimed to assess the impact of different compositions of organic mulch, derived from water hyacinth and banana stems, combined with a blend of chicken and cow manure on lettuce growth and yield. Employing ANOVA analysis at a 5% significance level, with a DMRT follow-up test, the research involved seven treatments and two controls. The treatments included organic mulch without manure mixture (M1), and organic mulch with 5% (M2), 10% (M3), 15% (M4), 20% (M5), 25% (M6), and 30% (M7) cow and chicken manure. Positive control was Black Silver Plastic Mulch, and negative control was without mulch. The study revealed significant effects of organic mulch treatments on plant height, leaf count, and crop diameter during the initial vegetative growth stage. Specifically, treatment M5, comprising organic mulch from water hyacinth with a 20% mixture of cow and chicken manure, demonstrated a notable increase in net head weight per plot at harvest. This suggests the potential of this particular mulch composition for enhancing lettuce yield. The findings emphasize the practical application of organic mulch, particularly M5, as a beneficial strategy in lettuce cultivation, promoting growth and ultimately increasing harvest yield.